UNIT 2.23 High‐Throughput, Cell‐Based Screens to Identify Small‐Molecule Inhibitors of Ricin Toxin and Related Category B Ribosome Inactivating Proteins (RIPs). Issue 1 (February 2013) - Wahome, Paul G.; Mantis, Nicholas J.
Abstract: Ricin is a member of the ubiquitous ribosome‐inactivating protein (RIP) family of toxins. The Centers for Disease Control and Prevention (CDC) classify ricin and related toxins as Category B biothreat agents. There are currently no antidotes or therapeutics to counteract RIPs in humans. The discovery of effective small‐molecule inhibitors of RIPs is increasingly possible, however, due to the availability and accessibility of diverse small‐molecule chemical libraries coupled with robust robotics and automated screening methodologies. In this article, we describe a cell‐based, high‐throughput screening strategy and secondary assays that we have successfully used to identify compounds that target ricin toxin's enzymatic activity and intracellular trafficking, as well as stress‐activated signaling pathways associated with cell death. The methods described in the protocol are amenable to the other RIPs. Curr. Protoc. Toxicol. 55:2.23.1‐2.23.14. © 2013 by John Wiley & Sons, Inc.